1998
DOI: 10.1136/vr.142.4.86
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic induced congenital malformations in sheep embryos using netobimin

Abstract: Benzimidazole compounds have teratogenic effects in domestic and experimental animals. In this study, 14 Manchega ewes were treated orally, under controlled conditions, with 20 mg netobimin (a prodrug of a benzimidazole compound) per/kg bodyweight on the 17th day of pregnancy. Congenital malformations and abortions affected 60 per cent of the lambs. The main malformations were skeletal and renal, but vascular malformations were observed for the first time. The abnormalities were investigated using radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…Different studies have shown teratogenic effects of the anthelmintic benzimidazoles Cristofol et al, 1995;Navarro et al, 1998;Teruel et al). The teratogenic activity of ABZ in vivo is attributed to its active albendazole sulphoxide (ABZSO) metabolite which has the capacity of reaching the embryos in elevated concentrations (Cristofol et al, 1995(Cristofol et al, , 1997Capece et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown teratogenic effects of the anthelmintic benzimidazoles Cristofol et al, 1995;Navarro et al, 1998;Teruel et al). The teratogenic activity of ABZ in vivo is attributed to its active albendazole sulphoxide (ABZSO) metabolite which has the capacity of reaching the embryos in elevated concentrations (Cristofol et al, 1995(Cristofol et al, , 1997Capece et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Among the anthelmintic agents, benzimidazoles present a broad spectrum of activity with high effectiveness and safety (Campbell, 1990), however administered during gestation, they have demonstrated teratogenic effects such as external, skeletal and vascular abnormalities (Cristofol et al, 1997;Navarro et al, 1998Navarro et al, , 1999Teruel et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The possible resorptions were analyzed after inspection of ovaries and uterus. All fetuses were analyzed for skeletal malformation according to Navarro et al (1998) [3]. The litter was considered as a unit of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Among the anthelmintic agents, benzimidazole presents a broad spectrum of activity with high effectiveness and safety (Campbell, 1990) gestation, it has demonstrated teratogenic effects such as external, skeletal and vascular abnormalities (Cristófol et al, 1997;Navarro et al, 1998Navarro et al, , 1999Teruel et al, 2003Teruel et al, , 2009aCapece et al, 2003;Moreti et al, 2005). Several studies suggest that the capacity of benzimidazolic drugs to bind with the tubulin of cells is responsible for the toxic effects observed during gestation (Delatour & Parish, 1986;Piscopo & Smoak, 1997) and its efficacy is attributed to its active albendazole sulphoxide metabolite (ABZSO), owing to its higher systemic availability compared to ABZ (Delatour et al, 1984).…”
Section: Introductionmentioning
confidence: 99%